Systemic Chemotherapy and Two-Stage Hepatectomy for Extensive Bilateral Colorectal Liver Metastases - Chun, Yun Shin (2007)
Background Two-stage hepatectomy has been proposed for patients with bilateral colorectal liver metastases (CLM). The aim of this study was to compare the outcome of patients with CLM treated with preoperative chemotherapy followed by one- or two-stage hepatectomy. Methods From a prospective database, 214 consecutive patients who received preoperative systemic chemotherapy (fluoropyrimidine with irinotecan or oxaliplatin) followed by planned one- or two-stage hepatectomy were retrospectively analyzed (1998–2006). In patients undergoing two-stage procedures, minor hepatectomy (wedge or segmental resection[s]) was systematically performed before major (more than three segments), second-stage hepatectomy. Preoperative portal vein embolization (PVE) was performed if indicated. Results One- (group I) and two-stage(group II) hepatectomies were performed in 184 and 21 patients, respectively. Median number of metastases in groups I and II were two (range 1–20) and seven (range 2–20). All patients in group II had bilateral disease vs 39% in group I. Major hepatectomy was performed in all patients in group II and 79% in group I. PVE was performed in 18 group I and 12 group II patients without increase in morbidity. For group I, group II first stage, and group II second stage, respectively, morbidity (24%, 24%, 43%), median hospital stay (7 days, 6 days, 6.5 days) and 30 days postoperative mortality (2%, 0%, 0%) were not significantly different (P = NS). Median follow-up was 25 months; median survival has not been reached. One- and 3-year overall and disease-free survival rates from the time of hepatic resection were 95% and 75%, 63% and 39%, respectively in group I; 95% and 86%, 70% and 51%, respectively in group II (P = NS). Conclusions Two-stage hepatectomy with preoperative chemotherapy results in comparable morbidity and survival rates as one-stage hepatectomy. This approach enables selection and treatment of patients with multiple, bilateral CLM who will benefit from aggressive surgery with good outcomes.